2021
DOI: 10.1097/pts.0000000000000893
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Elderly Fallers: Identifying Associated Risk Factors for 30-Day Unplanned Readmissions Using a Clinical Data Warehouse

Abstract: Identifying associated risk factors for 30-day unplanned readmissions using a clinical data warehouse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…These included older age, male gender, comorbidities, higher ISSs, and being on public insurance 5,9,10,19,20 . Our study showed that these factors are quite similar in the elderly population, and therefore, this reinforces need to adjust for patient mix when using hospital readmissions as a metric for performance 8,21 …”
Section: Discussionsupporting
confidence: 54%
“…These included older age, male gender, comorbidities, higher ISSs, and being on public insurance 5,9,10,19,20 . Our study showed that these factors are quite similar in the elderly population, and therefore, this reinforces need to adjust for patient mix when using hospital readmissions as a metric for performance 8,21 …”
Section: Discussionsupporting
confidence: 54%
“…Ishaemic events: acute myocardial infarction, acute stroke, acute kidney injury stage III, acute mesenteric ischaemia and acute peripheral vascular ischaemia 25. Other complications: acute exacerbation of COPD,26 acute heart failure27 and falls 28…”
Section: Methods and Analysismentioning
confidence: 99%
“…25 Other complications: acute exacerbation of COPD, 26 acute heart failure 27 and falls. 28 Before each follow-up period, the participants or their relatives will be contacted via email, letter or phone to check if the primary endpoint was reached. If one of the outcome components is reached, the trial will be closed for that patient.…”
Section: Primary Outcomementioning
confidence: 99%
“…Loss of resources including friends and family due to death may lead to isolation 13 . Loss of the resources of health and agility leads to a loss of physical independence 14-16 . The inability to drive may lead to further loss causing isolation and the loss of hobbies 16-18 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%